Role of defects in ultra-high gain in fast planar tin gallium oxide UV-C photodetector by MBE - Mukhopadhyay, Partha; Hatipoğlu, İsa; Frodason, Ymir K.; Varley, Joel B.; Williams, Martin S. (AIP Publishing, 2022)
We report ultra-high responsivity of epitaxial (SnxGa1-x)(2)O-3 (TGO) Schottky UV-C photodetectors and experimentally identified the source of gain as deep-level defects, supported by first principles calculations. Epitaxial TGO films were grown by plasma-assisted molecular beam epitaxy on (similar to 201) oriented n-type beta-Ga2O3 substrates. Fabricated vertical Schottky devices exhibited peak responsivities as high as 3.5 x10(4) A/W at -5 V applied bias under 250 nm illumination with sharp cutoff shorter than 280 nm and fast rise/fall time in milliseconds order. Hyperspectral imaging cathodoluminescence (CL) spectra were examined to find the mid-bandgap defects, the source of this high gain. Irrespective of different tin mole fractions, the TGO epilayer exhibited extra CL peaks at the green band (similar to 2.20 eV) not seen in beta-Ga2O3 along with enhancement of the blue emission-band (similar to 2.64 eV) and suppression of the UV emission-band. Based on hybrid functional calculations of the optical emission expected for defects involving Sn in beta-Ga2O3, V-Gn-Sn complexes are proposed as potential defect origins of the observed green and blue emission-bands. Such complexes behave as acceptors that can efficiently trap photogenerated holes and are predicted to be predominantly responsible for the ultra-high photoconductive gain in the Sn-alloyed Ga2O3 devices by means of thermionic emission and electron tunneling. Regenerating the V G . Sn defect complexes by optimizing the growth techniques, we have demonstrated a planar Schottky UV-C photodetector of the highest peak responsivity. Published under an exclusive license by AIP Publishin
Keywords: TOTAL-ENERGY CALCULATIONS; SEMICONDUCTORS